2012
DOI: 10.1007/s12015-012-9375-6
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells for Cardiac Therapy: Practical Challenges and Potential Mechanisms

Abstract: Cell based treatments for myocardial infarction have demonstrated efficacy in the laboratory and in phase I clinical trials, but the understanding of such therapies remains incomplete. Mesenchymal stem cells (MSCs) are classically defined as maintaining the ability to generate mesenchyme-derived cell types, namely adipocytes, chondrocytes and osteocytes. Recent evidence suggests these cells may in fact harbor much greater potency than originally realized, as several groups have found that MSCs can form cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
68
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 60 publications
0
68
0
1
Order By: Relevance
“…Although animal studies clearly indicated that the engraftment and differentiation specify the regenerative mechanism, 35,36 the paracrine effect is today also recognized as part of the overall regenerative process. 2,[37][38][39][40][41][42] In this context, our present study underscores the capacity of allogeneic hCPC to elicit Treg response as an indirect paracrine effect that would promote cardiac repair and suggests that the presumed functional benefit of allogeneic CPC could be also linked to their inherent immune properties. This notion is reinforced by our results showing that in allogeneic settings hCPC can inhibit an ongoing inflammatory T-cell response.…”
Section: Discussionmentioning
confidence: 58%
“…Although animal studies clearly indicated that the engraftment and differentiation specify the regenerative mechanism, 35,36 the paracrine effect is today also recognized as part of the overall regenerative process. 2,[37][38][39][40][41][42] In this context, our present study underscores the capacity of allogeneic hCPC to elicit Treg response as an indirect paracrine effect that would promote cardiac repair and suggests that the presumed functional benefit of allogeneic CPC could be also linked to their inherent immune properties. This notion is reinforced by our results showing that in allogeneic settings hCPC can inhibit an ongoing inflammatory T-cell response.…”
Section: Discussionmentioning
confidence: 58%
“…Despite corneal transplantation is the most successful solid organ transplantation, immune rejection is still the major cause of graft failure. Over the last decade, mesenchymal stem cell (MSC) therapy has been proposed and used as a possible treatment strategy for cardiovascular diseases, renal wound repair, diabetes, systemic lupus erythematosus, and solid organ transplantation [4][5][6][7] . MSCs are a promising stem cell population because of their self-renewal, pluripotential capability, low immunogenicity properties, and notable immunomodulatory and anti-inflammatory activities [8] .…”
Section: Introductionmentioning
confidence: 99%
“…The MSC population offers an exciting possibility for cellular-based therapies due to their unique attributes of multipotency and presence in the adult. Although recent findings of MSC-mediated cardiac repair are very encouraging, the understanding of MSC biology remains incomplete, partly reflecting limitations of available in vitro culture systems (Cashman et al, 2012). Each cell type has its own advantages, but there are still numerous issues to consider, such as cell number, ability to differentiation, immune rejection, teratoma formation, and ethical issues (Gnecchi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%